Oral health related quality of life is affected by disease activity in Behcet's disease - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2006)
OBJECTIVES: This study aimed to investigate oral and general health related quality of life (QoL) in patients with Behcet's Disease (BD) and to assess the performance of Turkish versions of oral health related quality questionnaires. SUBJECTS AND METHODS: Ninety-four BD patients, 24 patients with recurrent aphthous stomatitis (RAS), 113 healthy controls (HC) and 44 dental patients were investigated. QoL was assessed by oral health impact profile-14 (OHIP-14), oral health related quality of life (OHQoL) and short form-36 (SF-36) questionnaires. RESULTS: OHQoL, OHIP-14 and SF-36 subscale scores were significantly worse in patients with BD compared with those in HC (P < 0.05). Both OHIP-14 and OHQoL scores were significantly worse in active patients compared with inactives in BD and RAS (P < 0.05). Scores of SF-36 Role physical, Role emotional and Vitality were also lower in active patients than in inactives in BD (P < 0.05). Scores of OHIP-14 and OHQoL were significantly worse in patients treated with colchicine compared with those treated with immunosuppressives (P < 0.05). CONCLUSIONS: Both oral and general QoL was impaired in BD and associated with disease activity and treatment modalities. Translated Turkish versions of OHIP-14 and OHQoL were also observed to be valid and reliable questionnaires for further studies.
Keywords: quality of life; disease activity; treatment modalities; Behcet's disease; CENTERED OUTCOME MEASURES; NECK RADIOTHERAPY; IMPACT PROFILE; VALIDATION; SEVERITY; HEAD